MESSAGE TO CHILDREN IN THE FILM NUSSA AND RARRA “ANTTA HILANG” - Kanaya Siti Nur Syari'ah; Ahmad falahudin; Alya Sabrina Mujakirahmah; Ijang Yedi Yusuf; Maghfira Iqra Yurisa (Universitas Pendidikan Indonesia, 2021)
The purpose of this study was to take the film Nusa and Rarra because this film contains many messages and values, Islamic morals that have been taught by the Prophet Muhammad SAW. Nussa is an Indonesian animated series produced by animation studio The Little Giantz and 4Stripe Productions. Animation means to animate, give soul and move inanimate objects. Animation is the process of making objects that were originally inanimate objects, then arranged in different positions as if they were alive. The method used is a qualitative research method with a semiotic approach. Through image analysis, Islamic moral meaning is sought. The objects studied are Symbols, Indexes, and Icons. The main data of this research is the visualization of the characters of Nussa and Rarra which is sourced from one of the Nussa Official Youtube videos entitled